2003
DOI: 10.1227/01.neu.0000044460.17286.11
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted Thoracoscopic Resection of a Benign Mediastinal Neurogenic Tumor: Technical Note

Abstract: This case report demonstrates the feasibility of robot-assisted thoracoscopic extirpation of a thoracic neurogenic tumor. Robot-assisted surgery may prove to be of additional value in challenging thoracoscopic surgery, such as the delicate surgical removal of benign neurogenic tumors, because of the support in manipulation and visualization during videoscopic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 12 publications
1
30
0
2
Order By: Relevance
“…4,5,19 To our knowledge, there has been no description in the literature regarding this approach applied to neurogenic tumors at the extreme locations (the very top and bottom of the posterior mediastinum). Indeed, the presence of schwannomas in these regions is rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,19 To our knowledge, there has been no description in the literature regarding this approach applied to neurogenic tumors at the extreme locations (the very top and bottom of the posterior mediastinum). Indeed, the presence of schwannomas in these regions is rare.…”
Section: Discussionmentioning
confidence: 99%
“…The da Vinci robot has recently been used to treat posterior mediastinal schwannomas in a single-stage operation with excellent surgical outcomes. 4,5,19 However, most existing reports on robotic schwannoma resection have involved the midthoracic region. Here, we present 2 illustrative cases of thoracoscopic schwannoma resection at the cranial and the caudal extremes of the chest cavity using the da Vinci robotic system.…”
mentioning
confidence: 99%
“…In neurosurgery, robot applications mainly directed to stereotactic and endoscopic procedures have been pioneered by innovative neurosurgeons in the past two decades [14,15] . More recently, clinical applications of robotic neurosurgical telemanipulation have been reported by several groups [16][17][18] . Although the practical applications of robotic-assisted procedures in neurosurgery are yet to be demonstrated, as technology continues to advance, robotic applications in neurosurgery are likely to become more prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…Ruurda et al demonstrated the feasibility of a robotassisted thoracoscopic resection of a benign neurogenic tumor in the posterior mediastinum in 2003 [31]. The patient was placed in a semilateral position and several additional auxiliary trocars had to be placed for lung retraction.…”
Section: Posterior Mediastinummentioning
confidence: 99%